2020
DOI: 10.1101/2020.06.30.20143701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics, outcome and predictors of in-hospital mortality in an elderly population from a SARS-CoV-2 outbreak in a long-term care facility

Abstract: Since December 2019, coronavirus disease 2019 (COVID-19) pandemic has spread from China all over the world, many COVID-19 outbreaks have been reported in long-term care facilities (LCTF). However, data on clinical characteristics and prognostic factors in such settings are scarce. We conducted a retrospective, observational cohort study to assess clinical characteristics and baseline predictors of mortality of COVID-19 patients hospitalized after an outbreak of SARS-CoV-2 infection in a LTCF. A total… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We feel that hyperinflammation was pathogenically linked to both myocardial infarction and AIHA. Indeed, in our cohort, IL-6 appeared to be an independent predictor of death, together with elevated CRP [19].…”
Section: Discussionsupporting
confidence: 46%
“…We feel that hyperinflammation was pathogenically linked to both myocardial infarction and AIHA. Indeed, in our cohort, IL-6 appeared to be an independent predictor of death, together with elevated CRP [19].…”
Section: Discussionsupporting
confidence: 46%
“…A few studies showed that individuals with obesity may decrease in‐hospital mortality 31,75,87,89 . Some studies showed that obesity may insignificantly decrease 41,47,81,90 or increase 55,67,68,84,91–96 the odds of death among individuals with obesity. The majority of studies showed that obesity significantly increased the odds of death among COVID‐19 patients with obesity.…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…The present study suggests that, at least in elderly patients with COVID-19, adequate controlled diabetes at the time of admission and during hospitalization might reduce the risk of in-hospital mortality associated with T2D. This interpretation may explain why T2D per se was not demonstrated to be an independent predictor of death in our previous analysis in the same patients [16], in apparent contrast with other studies [17]. Zhu et al [18] have recently described, in a retrospective longitudinal study, that well-controlled blood glucose (blood glucose values within 70 to 180 mg/dl) was associated with markedly lower mortality compared to individuals with poorly controlled blood glucose (blood glucose values exceeding 180 mg/dl).…”
Section: Discussionmentioning
confidence: 48%
“…An alternative interpretation for the lack of an association between T2D and mortality could be that possible pre-existing complications of T2D are more important. In apparent support to this interpretation, in our previous analysis [16], CV diseases (and not T2D) emerged as an independent predictor of death over T2D per se. More in general, cardiovascular disease is a predictor of mortality in infected patients regardless of diabetes and even in non COVID-19 patients [21].…”
Section: Discussionmentioning
confidence: 59%